Struktur dan Hierarki Ilmu (al-Ghazali dan al-Farabi) - Herman, Muhammad Akbar; M, Marilang; Nonci, Muhammad Hajir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to understand the meaning of the structure and hierarchy of science, the structure and hierarchy of science according to al-Ghazali, and the structure and hierarchy of science according to al-Farabi. The results of this research show: 1) The structure of science is a systematic collection of knowledge consisting of components that are interrelated or coordinated so that they can become a theoretical basis or provide an explanation. The hierarchy of knowledge is a sequence or level of knowledge; 2) Regarding scientific terminology, Al-Ghazali tries to map it into three global categories based on the level of obligation, source, and social function. In an ontological perspective, Al-Ghazali divides science into Fardhu 'Ain and Fardhu Kifayah. In the epistemological framework, science, according to Al-Ghazali, can be mapped into two, namely Sharia Science and Sharia Ghairu. In Al-Ghazali's reading, all knowledge that is included in the framework of sharia science is commendable. However, this is not the case with knowledge that falls within the domain of sharia-ghiru science. This knowledge is mapped into three domains, namely: praiseworthy, disgraceful, and neutral (mubah); 3) Al-Farabi classified science into two large groups, namely 'Aqliyyah (intellectual) sciences, which were then called Philosophical Sciences, and Naqliyyah (doctrinal) sciences, which were then called Religious Sciences.